Preventing ankle sprains and improving balance in tennis players - Malliou, V. J.; Malliou, P.; Gioftsidou, A.; Douvis, S.; Mavvidis, A. (Medicine and Science in Tennis, 2008)
The aim of the present paper was to present a structured programme of how to incorporate specific balance exercises for tennis players to improve balance and prevent lower limb injuries.